THE EVALUATION OF INTERNAL CONTROL IMPLEMENTATION OVER MERCHANDISE INVENTORY AT PT. SURAMANDO (PHARMACEUTICAL DISTRIBUTORS AND GENERAL SUPPLIERS) IN MANADO - Seredei, Srijantri; Runtu, Treesje (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Inventory is a firms current assets, that its amount is material and constituting one of essential factor in the corporate operational activity. That is why a good internal controls to must be done secure supplies from the acts of fraud, deviation and damage. The purpose of this study is to evaluate the internal control over merchandise inventory at PT. Suramando it is running well. The method used is qualitative method through descriptive analysis. The final conclusion is that based on the elements of internal control from the control environment, risk assessment, control activities, information and communication, and monitoring the inventory of merchandise at PT. Suramando is already effective, where the separation between the functions is associated with the receiving and selling of goods. Monitoring of inventory is also done every day. In addition, the presence of security guards and CCTV cameras make inventory more secure. The management of PT. Suramando should improve risk assessment and control the security of inventory to be more secure. Keywords: internal control,Â  inventory